2001
DOI: 10.1001/jama.285.6.769
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Fruits and Vegetables and Risk of Breast Cancer

Abstract: HE ASSOCIATION BETWEEN FRUITand vegetable consumption and breast cancer risk has been examined in more than 25 case-control studies, but relatively few cohort studies.1 A recent summary of 19 case-control and 3 cohort studies concluded that elevated fruit and vegetable consumption probably reduces breast cancer risk. Approximately half of the reported associations for all types of fruit and vegetable groups combined showed at least a 25% reduction in breast cancer risk, whereas few associations showed more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
2
5

Year Published

2001
2001
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(173 citation statements)
references
References 29 publications
5
161
2
5
Order By: Relevance
“…29 The lack of association between fruit and vegetable intake in childhood and breast cancer risk supports the result of a recent meta-analysis of cohort studies of adult diet and breast cancer risk. 30 Epidemiological evidence of a protective role of vitamin E intake against breast cancer in adult studies is weak, 2 31 although lower prostate cancer risk associated with vitamin E supplementation has been reported from a large randomised controlled trial. 32 The higher risk of breast cancer associated with increasing intake of retinol is surprising and in contrast with the weak but consistent observational evidence that higher intake of vitamin A, including preformed retinol, is associated with lower risk of breast cancer.…”
Section: Previous Studiesmentioning
confidence: 99%
“…29 The lack of association between fruit and vegetable intake in childhood and breast cancer risk supports the result of a recent meta-analysis of cohort studies of adult diet and breast cancer risk. 30 Epidemiological evidence of a protective role of vitamin E intake against breast cancer in adult studies is weak, 2 31 although lower prostate cancer risk associated with vitamin E supplementation has been reported from a large randomised controlled trial. 32 The higher risk of breast cancer associated with increasing intake of retinol is surprising and in contrast with the weak but consistent observational evidence that higher intake of vitamin A, including preformed retinol, is associated with lower risk of breast cancer.…”
Section: Previous Studiesmentioning
confidence: 99%
“…However, most of these studies used casecontrol designs, which are subject to recall bias. Findings from prospective cohort studies of fruits and vegetables in stomach, breast, and colorectal cancer have generated weaker results (World Cancer Research Fund & American Institute for Cancer Research, 1997;Smith-Warner et al, 2001b;Terry et al, 2001c;IARC, 2003). In addition, an intervention study of fruits and vegetables on recurrence of colorectal adenomas did not find a reduction in risk .…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Although multiple factors appear to increase the risk of breast cancer, diet is one of the most important lifestyle factors associated with it (Doll & Peto, 1981;Willett, 1995;Rock et al, 1997). The evidence from epidemiological studies is based mainly on observations and case-control studies, in which recall and selection bias may influence the results (Smith-Warner et al, 2001). Pooled analysis of cohort studies has not shown clear evidence for effects of dietary modification in the adulthood to associate with reduced breast cancer risk (Smith-Warner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence from epidemiological studies is based mainly on observations and case-control studies, in which recall and selection bias may influence the results (Smith-Warner et al, 2001). Pooled analysis of cohort studies has not shown clear evidence for effects of dietary modification in the adulthood to associate with reduced breast cancer risk (Smith-Warner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%